PERANCANGAN SISTEM INFORMASI KURSUS DI SEKOLAH TINGGI ILMU KOMPUTER CIPTA KARYA INFORMATIKA - Srisulistiowati, Dwi Budi (Universitas Dirgantara Marsekal Suryadarma, 2014)
Growth of information world in this time faster enter various good area in knowledge and science, at the moment experience of very technological to fast progress especially base on and computer of internet. Just as in course needing accurate data get information in each every it its. With media of Internet the expense of marketing for the promotion of Company Profile can be depressed as small as possible. And its goals can for society in general and wide from various existing heterogeneous coat.